Biohybrid Microtube Swimmers Driven by Single Captured Bacteria. Issue 19 (16th March 2017) - Stanton, Morgan M.; Park, Byung‐Wook; Miguel‐López, Albert; Ma, Xing; Sitti, Metin; Sánchez, Samuel
Abstract : Bacteria biohybrids employ the motility and power of swimming bacteria to carry and maneuver microscale particles. They have the potential to perform microdrug and cargo delivery in vivo, but have been limited by poor design, reduced swimming capabilities, and impeded functionality. To address these challenge, motile Escherichia coli are captured inside electropolymerized microtubes, exhibiting the first report of a bacteria microswimmer that does not utilize a spherical particle chassis. Single bacterium becomes partially trapped within the tube and becomes a bioengine to push the microtube though biological media. Microtubes are modified with "smart" material properties for motion control, including a bacteria‐attractant polydopamine inner layer, addition of magnetic components for external guidance, and a biochemical kill trigger to cease bacterium swimming on demand. Swimming dynamics of the bacteria biohybrid are quantified by comparing "length of protrusion" of bacteria from the microtubes with respect to changes in angular autocorrelation and swimmer mean squared displacement. The multifunctional microtubular swimmers present a new generation of biocompatible micromotors toward future microbiorobots and minimally invasive medical applications. Abstract : For a new biohybrid microswimmer design, single swimming E. coli bacteria are captured inside polydopamine modified microtubes. Bacteria flagella drive the microtube through liquid media and demonstrate directional swimming that can be terminated with a chemically activated switch. Swimming behavior is investigated to understand its feasibility for potential future biomedical applications.